Seed Source Variation as Observed under Scanning Electron Microscope in Leaf Characters of Dalbergia sissoo Roxb. - Gera, Mohit; Gera, Neelu; Agarwal, Rashmi; Gupta, B. N. (Indian Forester, 2004)
Twenty seed sources of Dalbergia sisson Roxb. Scattered over a wide range of its occurrence in India were studied for the pattern of variation in micro leaf characters, viz., upper stomatal frequency, lower stomatal frequency, upper stomatal size and lower stomatal size under scanning electron microscope (SEM). The subjective observations were also recorded on other micro leaf characters such as nature and type of cuticle, stomatal openings and presence of macro/micro-hairs. The results revealed the presence of highly significant variations among the characters studied. All the quantitative characters observed under SEM showed higher values for genotypic variance and genotypic coefficient of variation as compared to the corresponding values of environmental variance and environmental caefficient of variation. There were also accompanied by high values of heritability and large amounts of genetic gain, indicating that these parameters are under strong genetic control, which can be exploited successfully for selection and further genetic improvement in this species. Lower values of stomatal frequency on lower leaf surface were recorded in the seed sources from Muzaffarnagar, Lucknow, Hyderabad and Kanpur, which has performed well in the filed. This is explained by the fact that the low stomatal frequency ofthe lower surface has led to conservation of moisture in the plants being tested under un-irrigated and semi-arid conditions. This has resulted into enhanced growth in these seed sources. The thickness of cuticle also appears to have contributed to the control of water loss from the underlying cells.